Surgical advances in the management of placenta accreta spectrum: establishing new expectations for operative blood loss. (2nd December 2022) - Cojocaru, Liviu; Lankford, Allison; Galey, Jessica; Bharadwaj, Shobana; Kodali, Bhavani S.; Kennedy, Kelly; Goetzinger, Katherine; Turan, Ozhan M.
Abstract: Objective: To evaluate whether the implementation of our surgical approach, referred to in the text as Linear Cutter Vessel Sealing System (LCVSS) technique, will improve perioperative outcomes in patients with placenta accreta spectrum (PAS), specifically by reducing blood loss and blood transfusion rates at the time of cesarean hysterectomy (C-HYST). The LCVSS technique integrates the following: (1) hysterotomy performed using the Linear Cutter, (2) no placental manipulation, (3) cauterization of anatomically prominent vascular anastomosis using the handheld vessel sealing system, and (4) completion of bladder dissection until the cervico-vaginal junction before ligation and division of uterine arteries. Materials and methods: This is a retrospective cohort study that analyzed perioperative outcomes in patients undergoing C-HYST for PAS at a tertiary care center from 1 July 2014 to 1 December 2019. Comparisons were performed between cases managed with the use of the LCVSS technique (designated as LCVSS cohort) and those managed without the use of the LCVSS technique (designated as no technique cohort). The primary outcomes were cumulative blood loss (CBL) and total perioperative blood transfusion of ≥4 and ≥6 units of PRBCs. The secondary outcomes were intra- and postoperative complications. Continuous and categorical variables were compared according to the sample size and distribution. Binary logistic regression analysis was performed to predict confounders for blood transfusion of ≥4 units of PRBCs. Results: A total of 69 prenatally diagnosed PAS cases underwent C-HYST at the time of delivery. Forty-four cases that were performed using the LCVSS technique comprised the LCVSS cohort. The remaining 25 were marked as no technique cohort. CBL was significantly lower in the LCVSS cohort (1124 ml [300–4100] vs 3500 ml [650–10600]; p < .001). The rate of urinary tract injuries was similar (16%). The rate of postoperative complications and reoperation for intra-abdominal bleeding were lower but not significantly different in LCVSS cohort (9 vs 20% and 0 vs 8%, p = .26 and p = .12, respectively). There were no differences in neonatal outcomes. Conclusion: Implementation of this advanced surgical approach for PAS management resulted in reduced blood loss and blood transfusion rates in comparison with no technique cohort.